Early Childhood Counts : a Programming Guide on Early Childhood Care for Development. - Evans, Judith L. (WBI learning resources series., 2000)
This programming guide and the related resources on CD-ROM provide an extensive and rich collection of learning materials and examples of good practice from around the world, as well as a selected library of recent articles, reports, and research findings on early childhood care for development (ECCD). Section 1 defines ECCD, summarizes the arguments favoring it, outlines some principles of upon which projects and programs should be based, and suggests a variety of programming principles that should underlie the creation of early childhood efforts. Section 2 helps the reader create a program; it addresses needs assessment. Section 3 focuses on defining the goals and objectives of the early childhood program. Section 4 describes basic early childhood programming strategies that have been developed successfully in countries outside of the developing world. Templates, provided for each strategy presented, contain a set of questions in relation to that strategy, along with a discussion of each question and some recommendations for how the questions might be answered to ensure a quality a quality program. Section 5 addresses what will be offered to the beneficiary group, how it will be offered, and who will offer the services. Section 6 elaborates on the reasons evaluations, describes the types of evaluations, and suggests how to conduct an evaluation. Section 7 sums up some of the issues related to costing early childhood projects and programs.